COVID-19 and impact of psychological stress on cardiovascular disease - Bana, Tasnim; Hoare, Jacqueline; Letuka, Pheletso; Ntusi, Ntobeko (SA Heart Journal, 2020)
COVID-19 has caused a global pandemic of anxiety, fear and uncertainty. National lockdowns, high mortality, social isolation, economic recession, job losses and food insecurity resulting from COVID-19 are potent drivers of increased stress levels, anxiety and depression, and have placed a substantial strain on healthcare and economic systems. Depression, anxiety and physical isolation are strongly linked to incident cardiovascular disease (CVD) as well as poorer outcomes in established CVD – including coronary artery disease, stroke and heart failure. Acute stress-related disorders such as post-traumatic stress disorder, have been robustly and independently associated with multiple phenotypes of CVD, particularly in the first year after the psychiatric diagnosis. Unprecedented psychological stress imposed by COVID-19 on the global population bears the potential to cause a parallel epidemic of mental health disorders and a subsequent surge in CVD, warranting strategic planning by healthcare services to mitigate its impact. This potential for a mental health crisis would require both large-scale psychosocial interventions, and incorporation of mental healthcare into disaster management plans. Anxiety and depression, as the dominant emotional responses to the outbreak, warrant adequate training of healthcare personnel and the optimal use of technological advances to deliver acute mental healthcare interventions which are time-limited and culturally sensitive.